Transforming the Ledger through the Evolving Role of Artificial Intelligence in the Accounting Profession - Iyere Samuel Iheonkhan; Sulaiman Taiwo Hassan (International Journal of Science and Society (IJSS), 2025)
This concept paper explores how artificial intelligence (AI) is transforming the accounting profession. By conducting a thorough review of relevant literature, the study analyzes the multifaceted effects of AI technologies, particularly how they are reshaping the traditional functions and expectations of accountants. The findings identify three core areas of impact: One, the automation of repetitive tasks, such as data entry, validation, and transaction processing; Two, the advancement of analytical capabilities through tools like predictive analytics and decision-making support systems; and Three, the evolution of professional roles, emphasizing increased efficiency, scalability, and a shift toward more strategic, value-driven activities. These developments suggest a profession in transition—one where embracing AI is essential for staying relevant and leveraging its full potential to enhance productivity and insight.